Ethnomathematic exploration of Istana Kuning’s architecture in Central Kalimantan - Amalia, Bayu Nanda Rizky; Kusdinar, Uus (Indonesian Journal of Science and Mathematics Education, 2026)
Mathematics learning is often perceived as disconnected from students’ cultural contexts and real-life experiences, highlighting the need for approaches that relate mathematical concepts to local cultural environments. This study aims to explore the ethnomathematical elements found in the architecture of Istana Kuning in Central Kalimantan. This research employed a qualitative, ethnographic approach. Data were collected through direct observation of architectural elements, interviews with the management of Istana Kuning, and documentation. The collected data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing, and were validated through triangulation techniques. The results indicate that several architectural elements and ornaments of Istana Kuning contain mathematical concepts such as symmetry, similarity, and geometric transformations, including translation, reflection, and rotation. These concepts were identified in wall carvings, window bars, chair arrangements, and shield ornaments, all of which reflect cultural values of balance and harmony. These findings imply that Istana Kuning has the potential to serve as a contextual learning resource to support more meaningful mathematics learning grounded in local cultural wisdom.